Gatekeeper Pattern for Enhanced Security in Distributed Systems - Vibha Negi,; Pramod Negi, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
As modern systems grow more distributed—spanning cloud platforms, on-prem servers, and edge devices—keeping internal services secure has become a major challenge. Traditional network firewalls and perimeter defenses are no longer enough to stop attackers or prevent misuse. The Gatekeeper pattern offers a better solution: it acts as a smart checkpoint that sits in front of sensitive services, making sure every request is properly checked before it gets through. This paper introduces the Gatekeeper as a security design pattern that helps enforce authentication, authorization, logging, and monitoring in a consistent and centralized way. We explain how it works, how to implement it, and why it’s especially helpful in edge environments, where devices often run in less secure and more unpredictable conditions. The Gatekeeper pattern supports zero-trust principles and helps organizations improve their overall security, no matter where their systems run.
Keywords: Gatekeeper Pattern; Zero Trust Architecture; Access Control; Policy Enforcement; Authentication; Authorization; Identity Validation; Role-Based Access Control (RBAC); Attribute-Based Access Control (ABAC); Rate Limiting; Audit Logging; Distributed Systems Security; Hybrid Cloud Security; Cloud-Native Security; API Gateway Security; Edge Device Security; Microservices Security; Edge Computing; SaaS Security Patterns; Security Design Patterns; System Ingress Security; Reverse Proxy; Sidecar Pattern; Security Daemon; Middleware Security; Secure System Architecture; Open Policy Agent (OPA); XACML; NGINX Ingress Controller; Transport Layer Security; Trusted Platform Module (TPM); Secure Enclave; IoT Security; Industrial Gateway Security; Edge Deployment Strategy; API Security Best Practices; Offline Security Enforcement; Policy Centralization; Security Auditing; Centralized Logging; Threat Detection; Security Compliance; Incident Response